Pathology of Idiopathic Interstitial Pneumonias - Hashisako, Mikiko (Clin Med Insights Circ Respir Pulm Med, 2016)
The updated classification of idiopathic interstitial pneumonias (IIPs) in 2013 by American Thoracic Society/European Respiratory Society included several important revisions to the categories described in the 2002 classification. In the updated classification, lymphoid interstitial pneumonia (LIP) was moved from major to rare IIPs, pleuroparenchymal fibroelastosis (PPFE) was newly included in the rare IIPs, acute fibrinous and organizing pneumonia (AFOP) and interstitial pneumonias with a bronchiolocentric distribution are recognized as rare histologic patterns, and unclassifiable IIP (UCIP) was classified as an IIP. However, recent reports indicate the areas of concern that may require further evaluation. Here, we describe the histopathologic features of the updated IIPs and their rare histologic patterns and also point out some of the issues to be considered in this context.